1987
DOI: 10.1111/j.1365-2672.1987.tb02413.x
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella and campylobacter contamination of broiler chicken carcasses and scald tank water: the influence of water pH

Abstract: Scalding at 50 degrees +/- 0.5 degrees C, in water maintained at pH 9.0 +/- 0.2 by the addition of sodium hydroxide, had no effect on the incidence of salmonella or campylobacter contamination of chicken carcasses. There were significant reductions, however, in the numbers of these organisms in the water itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…Similar findings have been reported for other physical and chemical meth- ods of removing Campylobacter from chicken carcasses (13). Studies with Salmonella also suggest that the chicken skin provides an environment that confers nonspecific protection to bacteria from potentially harmful treatments (13,24). This is most likely due to the presence of feather follicles and folds on the skin surface that, along with oils and fats present, offer some protection from ice crystal formation, which is known to be a major cause of damage to cells undergoing the freezing process.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Similar findings have been reported for other physical and chemical meth- ods of removing Campylobacter from chicken carcasses (13). Studies with Salmonella also suggest that the chicken skin provides an environment that confers nonspecific protection to bacteria from potentially harmful treatments (13,24). This is most likely due to the presence of feather follicles and folds on the skin surface that, along with oils and fats present, offer some protection from ice crystal formation, which is known to be a major cause of damage to cells undergoing the freezing process.…”
supporting
confidence: 74%
“…Considering these data, it is possible that chicken skin has a protective effect on the Campylobacter cells. Similar findings have been reported for other physical and chemical meth- ods of removing Campylobacter from chicken carcasses (13). Studies with Salmonella also suggest that the chicken skin provides an environment that confers nonspecific protection to bacteria from potentially harmful treatments (13,24).…”
supporting
confidence: 70%
“…In contrast, pre-enrichment was found to have no effect on the isolation rate of C. jejuni from chicken skin (Humphrey & Lanning 1987) or sewage (Fricker 1987 To determine the possible practical significance of pre-enrichment at 37T, its use with artificially and naturally contaminated samples was examined. The effects of incubation temperature, both before and after heating or freezing, on growth and resistance patterns of two strains of C. jejuni were also investigated.…”
mentioning
confidence: 99%
“…Generally heat resistance is at its maximum at pH 7 and decreases as the pH shifts from neutrality (ICMSF, 1996). In addition, in that study (Humphrey and Lanning, 1987) it was reported that adjusting the scalding water tank to pH 9 significantly reduced bacterial numbers in the scalding water but not the bacterial count on the carcass. In addition, in that study (Humphrey and Lanning, 1987) it was reported that adjusting the scalding water tank to pH 9 significantly reduced bacterial numbers in the scalding water but not the bacterial count on the carcass.…”
Section: Effect Of Ph and Presence Of Acidsmentioning
confidence: 89%